IMPLEMENTASI PERATURAN MENTERI SOSIAL NOMOR 25 TAHUN 2019 TENTANG KARANG TARUNA (STUDI DI DESA TAPIAN NAULI KECAMATAN ULU BARUMUN KABUPATEN PADANG LAWAS) - Ranto Adiansyah; Anwar Saleh Hasibuan; Nurainun (JURNAL SOSIO-KOMUNIKA, 2022)
This research is motivated by the lack of role of Youth Organizations in Tapian Nauli Village, Ulu Barumun District, Padang Lawas Regency in carrying out their duties and functions in accordance with Minister of Social Affairs Regulation Number 25 of 2019 concerning Youth Organizations. The implementation of the Minister of Social Affairs Regulation in question is to develop the potential of the young generation and the community and no longer play an active role in preventing and overcoming social problems through social rehabilitation, social security, social empowerment, and social protection as well as national priority programs. The formulation of the problem in this research is how to implement the Minister of Social Affairs Regulation Number 25 of 2019 concerning Youth Organizations in Tapian Nauli Village, what are the obstacles to Karang Taruna in carrying out their duties and functions in Tapian Nauli village and a review of fiqh siyasah on the role of Youth Organizations. This type of research is field research, namely research conducted by means of a direct survey of the field, this location is carried out in Tapian Nauli Village, Kec. Ulu Barumu, Kab. Old Field. The population in this study were the coaches, administrators and members of the youth organization, namely the coach/village head 1 (one), head 1 (one), secretary 1 (one), treasurer 1 (one) and members of the youth group 6 (six). With a relatively small population of 10 people, the author makes the entire population a sample using the Total Sampling technique. The source of this author's data is primary data and secondary data which the writer then analyzes using qualitative descriptive analysis, while the data collection used is observation, interviews and documentation. Based on the results of research through observations, interviews and documentation, it can be seen that the implementation of the Minister of Social Affairs Regulation Number 25 of 2019 concerning Youth Organizations has not been realized or can be said to be no longer active, the constraint factors are the lack of guidance for the Village Head, lack of socialization or approach to the management of Karang Taruna to the community, the lack of openness of the Management with Karang Taruna Members and decreased interest of Youth in Youth Organizations.